LIVING LAW DALAM KHIȚBAH DAN LAMARAN PERSPEKTIF SOSIOLOGI HUKUM - Fathonah K. Daud; M. Ridlwan Hambali (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
This paper discusses the khiṭbah and engagement in the perspective of the sociology of law. The method is using a normative empirical juridical approach. This paper finds that the history of the practice of engagement or khitbah bigens with matchmaking of the sons and daughters of the prophet Adam as. Along with the development of the human population into ethnic groups and the development of the insight of society itself, new procedure and prohibitions emerged, including in choosing a patner. In addition the form of engagement into various ways of implementation. However, this engagement was later accommodated by Islam and has been stated in the Qur’an and Hadith which is termed khitbah. In practice there is a natural difference between khitbah and the engagement. Most of the customary applications by bringing along delivery and sometimes there are still gifts in the form of money or livestock. As is the tradition of engagement found in Indonesian society, such as Peningset (Javanese), the tradition of giving Belehan (Bojonegoro, East Java), neundeun omong(Sundanese), Merisik (Melayu-Riau), Marhusip (Batak), Maminang (Minangkabau) and Mappetuada (Bugis). However, both are still community practices that contain noble values and should be perpetuated in society.